First fossilized skin of a giant penguin from the Eocene of Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; de Los Reyes, Leonardo Martín; Santillana, Sergio; Reguero, Marcelo Alfredo (Lethaia)
An articulated wing belonging to Palaeeudyptes gunnari containing mineralized skin was found in Lutetian (middle Eocene) sediments from Seymour Island, Antarctica. It shows the connective tissues, morphology and density of the feather follicles, and a groove pattern left by the feather calami resting on the skin. Analysis of the preserved surfaces indicates a composition of calcium phosphate. This is the most complete and only articulated wing described for this species and represents the first record of a neornithine bird preserving three-dimensional integument. Plumage density of the wing MLP 14-I-10-22, estimated by counting the follicles under a stereoscopic microscope, is lower than that of the modern Emperor penguin. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: de Los Reyes, Leonardo Martín. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Santillana, Sergio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Reguero, Marcelo Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina